PERAN HUMAS DALAM MEMPUBLIKASIKAN KEGIATAN PEMERINTAH MELALUI MEDIA SOSIAL INSTAGRAM DI SEKRETARIAT DPRD KOTA LAHAT - Aalia Letiara Trisilia; Rina Pebriana (Jurnal Prodi Ilmu Komunikasi, 2023)
The purpose of this study is to analyze the role of Public Relations in publicizing government activities through Instagram social media at the DPRD Secretariat. This study uses a qualitative descriptive method with in-depth interview techniques with two public relations staff who are responsible for the DPRD Secretariat's Instagram account. The results of the study show that Public Relations has an important role in publicizing government activities through Instagram social media. Public Relations is responsible for managing and uploading content related to DPRD activities, including photos and videos, as well as writing informative and interesting captions. Public Relations also plays a role in promoting the DPRD Secretariat Instagram account so that it is more widely followed by the public. However, in its implementation, Public Relations still faces several challenges, such as limited human resources and lack of support from DPRD leaders. In addition, there are also problems in measuring the impact and effectiveness of publishing activities through Instagram. In this case, this study recommends that DPRD increase support for Public Relations in terms of human resources and equipment needed to properly manage Instagram accounts. The DPRD also needs to provide training and development to improve PR's ability to manage social media. Finally, the DPRD must evaluate and measure the impact of posting through Instagram to determine the effectiveness of their social media strategy.